Investigation of recovery mechanisms in dye sensitized solar cells. (April 2016) - Chiappara, C.; Figà, V.; Di Marco, G.; Calogero, G.; Citro, I.; Scuto, A.; Lombardo, S.; Pignataro, B.; Principato, F.
Highlights: Spontaneous recovery of the short-circuit current and the open-voltage in DSSC. This recovery does not depend on the temperature and electrolyte composition. Impedance spectroscopy shows the increasing of electrons lifetime in TiO2 . Abstract: We study the spontaneous recovery phenomenon displayed by solar cells sensitized with a ruthenium complex-based dye N719, which manifests with the increase over the time (from several minutes up to some days) of the short circuit current density J sc and the open circuit voltage V oc, during cell illumination. Under dark conditions the current decreases over time after the application of forward bias voltages. We investigate the effects of temperature and electrolyte composition by means of current–voltage measurements and electrochemical impedance spectroscopy, both under dark and illumination conditions. The main result is that the recovery of the performances depends on the charge transport mechanism at the TiO2 /electrolyte interface and is caused by the increasing of the electron lifetime in the titania. This effect could be explained by intercalation of ions H + present in the electrolyte that limits the recombination of electrons from TiO2 to the triiodide.